2000
DOI: 10.1080/026404100365018
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the psychometric properties of the Perceived Motivational Climate in Sport Questionnaire - 2 in a sample of female athletes

Abstract: We undertook two studies to determine the validity and reliability of the revised Perceived Motivational Climate in Sport Questionnaire (PMCSQ-2). In Study 1, 201 female athletes (mean age 16.4 years) were administered the initial version of the PMCSQ-2 and a measure of reported tension and pressure experienced in sport. Exploratory principal component analysis suggested that the PMCSQ-2 contained two higher-order scales (Task-Involving and Ego-Involving climates), each with three subscales (Task: Cooperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
434
3
73

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(556 citation statements)
references
References 1 publication
19
434
3
73
Order By: Relevance
“…This facet of the social environment could be considered one of the most crucial dimensions of a task-involving motivational climate (Ames, 1992;Newton, et al, 2000), This result is consonant with work conducted in physical education (e.g., Ntoumanis, 2001), academic (e.g., Ames, 1992), and sport (e.g., Kavussanu & Roberts, 1996) settings, showing perceptions of a task-involving environment to be positively associated with perceived competence. Demonstrating improvement and effort are probably more controllable sources of competence evaluation and may, thus, make it easier for individuals to feel good about their abilities in achievement contexts such as sport.…”
Section: Dimensions Of Coaching Behaviorsupporting
confidence: 60%
See 2 more Smart Citations
“…This facet of the social environment could be considered one of the most crucial dimensions of a task-involving motivational climate (Ames, 1992;Newton, et al, 2000), This result is consonant with work conducted in physical education (e.g., Ntoumanis, 2001), academic (e.g., Ames, 1992), and sport (e.g., Kavussanu & Roberts, 1996) settings, showing perceptions of a task-involving environment to be positively associated with perceived competence. Demonstrating improvement and effort are probably more controllable sources of competence evaluation and may, thus, make it easier for individuals to feel good about their abilities in achievement contexts such as sport.…”
Section: Dimensions Of Coaching Behaviorsupporting
confidence: 60%
“…Perceived support rather than objective social support was tapped, because the former generally seems to yield the strongest associations with health and adjustment criteria (Sarason, Sarason, & Pierce, 1994). All responses (except mastery focus, which was scored on a 5-point scale; Newton et al, 2000) were indicated on a 7-point scale ranging from strongly disagree (1) to strongly agree (7).…”
Section: Measures Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se utilizó la versión adaptada al contexto español (Cecchini, González, López Prado, y Brustad, 2005) del PMCSQ-2 de Newton, Duda, y Yin (2000). Este cuestionario estaba compuesto de un total de 33 ítems, 17 de los cuales medían la percepción de un clima tarea, mientras que los otros 16 evaluaban la percepción de un clima.…”
Section: Métodounclassified
“…No mention was made of specific behaviours that have been conceptualised as performance-based e.g., unequal attention devoted to students based on normative ability, emphasising positive outcomes derived without effort (cf. Ames, 1992;Newton, Duda, & Yin, 2000;Papaioannou, 1994). Observational and qualitative studies are necessary, in addition to those employing validated scales, to substantiate the links between teaching practices that promote performance approach goal striving and the development of particular self-beliefs in early adolescence.…”
Section: Relationships Between Achievement Goals and Self-perceptionsmentioning
confidence: 99%